Primary endovascular treatment of post-irradiated carotid pseudoaneurysm at the skull base with the Pipeline embolization device. (22nd May 2014) - Tsang, Anderson Chun-On; Leung, Kar-ming; Lee, Raymond; Lui, Wai-man; Leung, Gilberto Ka-Kit
Abstract : Background: A post-irradiated carotid pseudoaneurysm at the skull base can cause life-threatening blowout syndrome. Conventional treatments include parent vessel occlusion, endovascular coiling or covered stenting. Use of the Pipeline embolization device (PED) for pseudoaneurysm exclusion at the skull base is not well described. Objective: To report the clinical and angiographic outcome after using multiple PEDs to treat recently ruptured radiation-induced carotid pseudoaneurysms at the skull base. Methods: Retrospective review of the clinical and angiographic records of patients who received PEDs as primary treatment for skull base carotid pseudoaneurysm between April 1, 2011 to March 31, 2013. Results: Seven patients (five men, two women) with a mean age of 58 years (range 47–65) were treated in the study period. Primary treatment with the PED alone, with adjunct coil embolization in two patients, achieved immediate hemostasis in all patients, with no pseudoaneurysm rebleeding after a mean follow-up of 15.3 months (range 4–24 months). One patient had periprocedural cerebral infarction. Delayed internal carotid artery occlusion secondary to in-stent thrombosis occurred in three patients, one of whom had lacunar infarct and two remained asymptomatic. Conclusions: Endovascular treatment with the PED was effective in excluding skull base post-irradiated carotid pseudoaneurysms and preventing recurrent blowout. However, the risk of ischemic complications in this group of patients was high and our experience did not support the use of flow diverters as a first-line treatment for this condition.